Prenatal diagnosis by trio exome sequencing in fetuses with ultrasound anomalies: A powerful diagnostic tool - Tran Mau-Them, Frédéric; Delanne, Julian; Denommé-Pichon, Anne-Sophie; Safraou, Hana; Bruel, Ange-Line; Vitobello, Antonio; Garde, Aurore; Nambot, Sophie; Bourgon, Nicolas; Racine, Caroline; Sorlin, Arthur; Moutton, Sébastien; et al. (Frontiers in Genetics, 2023)
Introduction: Prenatal ultrasound (US) anomalies are detected in around 5 to 10% of pregnancies. In prenatal diagnosis, exome sequencing (ES) diagnostic yield ranges from 6% to 80% depending on inclusion criteria. We describe the first French national multicenter pilot study aiming to implement ES in prenatal diagnosis following detection of anomalies on US. Patients and methods: We prospectively performed prenatal trio-ES in 150 fetuses with at least two US anomalies or one US anomaly known to be frequently linked to genetic disorder. Trio-ES was only performed if the results could influence pregnancy management. Chromosomal microarray (CMA) was performed before or in parallel. Results: A causal diagnosis was identified in 52/150 fetuses (34%) with a median time to diagnosis of 28 days, rising to 56/150 (37%) after additional investigation. Sporadic occurrences were identified in 34/56 (60%) and unfavorable vital and/or neurodevelopmental prognosis in 13/56 (24%). The overall diagnostic yield was 41% (37/89) with first-line trio-ES versus 31% (19/61) after normal CMA. Trio-ES and CMA were systematically concordant for identification of pathogenic CNV. Conclusion: Trio-ES provided a substantial prenatal diagnostic yield, similar to postnatal diagnosis with a median turnaround of approximately 1 month, supporting its routine implementation when US detects prenatal anomalies.